Vitamin D Deficiency in Chronic Lymphocytic Leukaemia:Makurdi Perspective (Western Journal of Medical and Biomedical Sciences, 2025)
Vitamin D is a group of fat-soluble vitamins, commonly known for its critical role in calcium homeostasis and bone mineralization, but more recently it has been implicated in the pathogenesis of hematological cancers and shows promise as an anti-cancer therapy. Serum Vitamin D level has a positive relation with rate of disease progression in Chronic Lymphocytic Leukemia (CLL) and as such Vitamin D deficiency is a poor prognostic factor. This study is designed to evaluate the serum vitamin D concentration in CLL participants in comparison to age-matched non CLL participants. This was a cross-sectional study carried out among CLL patients seeking care in Benue state University Teaching Hospital. Thirty-six CLL patients and 36 healthy age and sex matched controls were recruited for the study. Their Full Blood Count and serum vitamin D levels were determined. Data obtained from the study were analysed using Statistical Package for Social Sciences (SPSS) version 23.0. The concentration of serum vitamin D in the CLL group was significantly lower than that of control. Prevalence of vitamin D deficiency was commoner in the CLL group (52.8%, n=19) compared to controls (5.6%, n=2), P
Keywords: Chronic lymphocytic leukaemia (CLL); Vitamin D